Host acceptance and oviposition behaviour of solitary wasp, Anisopteromalus calandrae (Howard) (Hymenoptera : Pteromalidae), A parasitoid of stored grain pests (Bangladesh Journal of Zoology, 2018)
The host acceptance and oviposition behaviour of the ectoparasitoid, Anisopteromalus calandrae (Howard) (Hymenoptera : Pteromalidae) was observed on unexposed (hidden) and exposed host of Sitophilus oryzae (L.) and Rhyzopertha dominica (F.) under laboratory conditions. The egg-laying behaviour was accomplished in eight phases in hidden hosts of S. oryzae i.e., inside wheat kernels but it was much shorter having five steps in those of exposed hosts. Average total time taken by a mated A. calandrae in unexposed host (inside wheat kernels) during different oviposition sequences was 55 minutes. On the other hand, average total time taken by a mated A. calandrae in exposed host of S. oryzae during oviposition sequences was 91.1 minutes. A. calandrae preferred fully developed S.oryzae grubs rather than half- grown pre-pupae and early pupae in exposed condition. Generally, eggs were laid on or near S. oryzae host larvae or pupae inside wheat kernel because of ectoparasitic nature of A. calandrae. More eggs are deposited in case of S. oryzae hosts at the abdominal region dorsally, sometimes eggs were laid on the meta-thoracic segment dorsally but rarely eggs were laid on late S. oryzae pupae prior to adult transformation. Oviposition by a mated A. calandrae female parasitoid was influenced by the host’s size and shape on exposed as well as unexposed (within seed kernel) conditions. Generally, the 3rd and the 4th instar larvae and pre-pupae of S. oryzae were preferred for egglaying in exposed condition. The parasite did not lay eggs on naked R. dominica larvae or pupae.Bangladesh J. Zool. 46(2): 205-216, 2018